Structural insights in cell-type specific evolution of intra-host diversity by SARS-CoV-2 - Kapil Gupta; Christine Toelzer; Maia Kavanagh Williamson; Deborah K. Shoemark; A. Sofia F. Oliveira; David A. Matthews; Abdulaziz Almuqrin; Oskar Staufer; Sathish K. N. Yadav; Ufuk Borucu; Frederic Garzoni; Daniel Fitzgerald; et al. (Nature Communications, 2022)
BriSΔ, a SARS-CoV-2 variant from clinical isolate hCoV/England/02/2020, comprises a deletion in a spike cleavage site. The structure and molecular dynamics of this spike provides mechanistic insights into how the deletion modulates virus infectivity.